Sleep disturbances in post-traumatic stress disorder - Moreira, Cátia Alves (2017)
Introduction: Post-traumatic stress disorder (PTSD) is characterized by a set of symptoms that occur following exposure to a traumatic event. These include re-experiencing the trauma, avoidance of stimuli related to it, and persistent symptoms of hypervigilance. PTSD is also associated with major sleep disturbances and these disturbances have a significant impact on quality of life and prognosis. Objectives: Our aim was to review the main changes in sleep pattern observed in bipolar disorder, the physiopathological mechanisms involved in those changes and their clinical impact. Methods: A non-systematic review of the literature in English was carried out by searching PubMed with the key words “sleep disturbance”, “post traumatic stress disorder” and “polysomnography”. Results: Complaints of altered sleep patterns include nightmares, insomnia, frequent nocturnal waking, poor sleep quality, a decrease in total sleep time (TST) and an increase in stage N1 of NREM sleep, with a decrease in stage N2. As regards REM sleep, previously mentioned changes previously observed on polysomnography (an increase in its density and percentage) proved inconsistent. Discussion and conclusions: Correcting the sleep disturbances observed in PTSD should be considered a therapeutic priority, as it prevents the recurrence of symptoms of the disorder and facilitates socio-professional integration, leading to greater success in rehabilitation and improved quality of life for these patients.